Students' Perceptions of the Effectiveness of Tutoring in Improving Academic Outcomes - David Darwin (Journal of Pedagogi, 2025)
This study aims to analyze students' perceptions of the effectiveness of tutoring in improving academic outcomes through a qualitative approach based on literature review. The main focus of this study is to understand how tutoring is perceived as a means of supporting academic achievement and increasing learning motivation. The literature review indicates that tutoring plays a crucial role in helping students overcome academic difficulties, improve learning skills, and strengthen their understanding of subject matter. According to Gagne (1985), an effective learning process depends on a supportive learning environment and teaching strategies that are adaptive to individual needs. The literature analysis also indicates that positive perceptions of tutoring are closely related to increases in students' average grades and self-confidence in learning. Furthermore, support from teachers and educational counselors plays a role in fostering independent learning habits and an orientation toward academic achievement. Based on the study's findings, the effectiveness of tutoring is determined not only by teaching methods but also by interpersonal interactions and the quality of communication between instructors and students. Therefore, a thorough understanding of students' perceptions of tutoring provides an important basis for designing more adaptive and sustainable educational strategies.